The contribution of homology arms to nuclease-assisted genome engineering - Baker, Oliver (Nucleic Acids Res, 2017)
Designer nucleases like CRISPR/Cas9 enable fluent site-directed damage or small mutations in many genomes. Strategies for their use to achieve more complex tasks like regional exchanges for gene humanization or the establishment of conditional alleles are still emerging. To optimize Cas9-assisted targeting, we measured the relationship between targeting frequency and homology length in targeting constructs using a hypoxanthine-guanine phosphoribosyl-transferase assay in mouse embryonic stem cells. Targeting frequency with supercoiled plasmids improved steeply up to 2 kb total homology and continued to increase with even longer homology arms, thereby implying that Cas9-assisted targeting efficiencies can be improved using homology arms of 1 kb or greater. To humanize the Kmt2d gene, we built a hybrid mouse/human targeting construct in a bacterial artificial chromosome by recombineering. To simplify the possible outcomes, we employed a single Cas9 cleavage strategy and best achieved the intended 42 kb regional exchange with a targeting construct including a very long homology arm to recombine ∼42 kb away from the cleavage site. We recommend the use of long homology arm targeting constructs for accurate and efficient complex genome engineering, particularly when combined with the simplifying advantages of using just one Cas9 cleavage at the genome target site.